Effect of outer boundary condition, reservoir size, and CO2 effective permeability on pressure and CO2 saturation predictions under carbon sequestration conditions. Issue 4 (4th February 2016) - Zhang, Liwei; Dilmore, Robert M.; Bromhal, Grant S.
Abstract: A TOUGH2 simulation was conducted to investigate how the change of key model parameters affects pressure and CO2 saturation response to CO2 injection into a deep CO2 storage reservoir. Given a domain of 100 × 100 km and a formation permeability of 10 −13 m 2, outer boundary condition does not have a significant impact on pressure increase and CO2 saturation results. In a simulation period of 30 years of CO2 injection + 100 years of post CO2 injection, with a total CO2 injection volume of 6.3×10 7 m 3 at T = 47°C and P = 10.5 MPa (equivalent mass of 30 million tonnes of CO2 ), there is no pressure difference between the no flow boundary case and the open boundary case given a domain size of 100 x 100 km (a total storage formation pore volume of 10 11 m 3 at T = 47°C and P = 10.5 MPa), and the maximum CO2 plume radius difference is 0.5%. However, given a domain size of 10 × 10 km, outer boundary condition significantly affects pressure simulation results. At t = 130 years, the pressure increase in the no flow boundary case is 56.5 times of the pressure increase in the open boundary case at the cell 50 m away from the injection well. For the 10 × 10 km case, the impact of outer boundary condition on CO2 saturation results is relatively small. The change in formation permeability significantly affects pressure increase results, while the change in CO2 relative permeability model only affects pressure increase results at cells close to the CO2 injector. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd